DEVELOPING STUDENTS’ SKILLS IN LEARNING FOREIGN LANGUAGES - Narziyeva Nargiza Ravilevna (TADQIQOTLAR, 2026)
This  article  explores  methods  and  strategies  for  developing  students’  skills  in learning  foreign  languages.  It  emphasizes  the  importance  of  communicative competence, cognitive development, and motivation in the language learning process. The study highlights practical approaches, including interactive activities, multimedia resources, and task-based learning, to enhance students’ proficiency and confidence in using a foreign language.